Sharp One-Parameter Mean Bounds for Yang Mean
Sharp One-Parameter Mean Bounds for Yang Mean
We prove that the double inequality<mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" id="M1"><mml:msub><mml:mrow><mml:mi>J</mml:mi></mml:mrow><mml:mrow><mml:mi>α</mml:mi></mml:mrow></mml:msub><mml:mo stretchy="false">(</mml:mo><mml:mi>a</mml:mi><mml:mo>,</mml:mo><mml:mi>b</mml:mi><mml:mo stretchy="false">)</mml:mo><mml:mo><</mml:mo><mml:mi>U</mml:mi><mml:mo stretchy="false">(</mml:mo><mml:mi>a</mml:mi><mml:mo>,</mml:mo><mml:mi>b</mml:mi><mml:mo stretchy="false">)</mml:mo><mml:mo><</mml:mo><mml:msub><mml:mrow><mml:mi>J</mml:mi></mml:mrow><mml:mrow><mml:mi>β</mml:mi></mml:mrow></mml:msub><mml:mo stretchy="false">(</mml:mo><mml:mi>a</mml:mi><mml:mo>,</mml:mo><mml:mi>b</mml:mi><mml:mo stretchy="false">)</mml:mo></mml:math>holds for all<mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" id="M2"><mml:mi>a</mml:mi><mml:mo>,</mml:mo><mml:mi>b</mml:mi><mml:mo>></mml:mo><mml:mn mathvariant="normal">0</mml:mn></mml:math>with<mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" id="M3"><mml:mi>a</mml:mi><mml:mo>≠</mml:mo><mml:mi>b</mml:mi></mml:math>if and only if<mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" id="M4"><mml:mi>α</mml:mi><mml:mo>≤</mml:mo><mml:msqrt><mml:mn mathvariant="normal">2</mml:mn></mml:msqrt><mml:mo>/</mml:mo><mml:mo stretchy="false">(</mml:mo><mml:mi>π</mml:mi><mml:mo>-</mml:mo><mml:msqrt><mml:mn mathvariant="normal">2</mml:mn></mml:msqrt><mml:mo stretchy="false">)</mml:mo><mml:mo>=</mml:mo><mml:mn mathvariant="normal">0.8187</mml:mn><mml:mo>⋯</mml:mo></mml:math>and<mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" id="M5"><mml:mi>β</mml:mi><mml:mo>≥</mml:mo><mml:mn mathvariant="normal">3</mml:mn><mml:mo>/</mml:mo><mml:mn mathvariant="normal">2</mml:mn></mml:math>, where<mml:math xmlns:mml="http://www.w3.org/1998/Math/MathML" id="M6"><mml:mi>U</mml:mi><mml:mo stretchy="false">(</mml:mo><mml:mi>a</mml:mi><mml:mo>,</mml:mo><mml:mi>b</mml:mi><mml:mo stretchy="false">)</mml:mo><mml:mo>=</mml:mo><mml:mo stretchy="false">(</mml:mo><mml:mi>a</mml:mi><mml:mo>-</mml:mo><mml:mi>b</mml:mi><mml:mo stretchy="false">)</mml:mo><mml:mo>/</mml:mo><mml:mo stretchy="false">[</mml:mo><mml:msqrt><mml:mn mathvariant="normal">2</mml:mn></mml:msqrt><mml:mrow><mml:mrow><mml:mi mathvariant="normal">arctan</mml:mi></mml:mrow><mml:mo></mml:mo><mml:mrow><mml:mo stretchy="false">(</mml:mo><mml:mo stretchy="false">(</mml:mo><mml:mi>a</mml:mi><mml:mo>-</mml:mo><mml:mi>b</mml:mi><mml:mo stretchy="false">)</mml:mo><mml:mo>/</mml:mo><mml:msqrt><mml:mn mathvariant="normal">2</mml:mn><mml:mi>a</mml:mi><mml:mi>b</mml:mi></mml:msqrt><mml:mo stretchy="false">)</mml:mo></mml:mrow></mml:mrow><mml:mo …